Nonlocal quasilinear variations of the Chafee-Infante problem - Moreira, Estefani Moraes (2023)
In this work, we developed some results on nonlocal quasilinear variations of the Chafee-Infante problem. In the non-autonomous quasilinear case, we will show the existence of special solutions known as non-autonomous equilibria. In the autonomous quasilinear case, we will exhibit the existence of a sequence of bifurcation of equilibria, for which we will analyze the stability and hyperbolicity. We will also exhibit the attractor of the global attractor for a particular case. In the last chapter, we will construct a concept of isolating block for multivalued problems and we will make an application of such concept.